Marker and real-time quantitative analyses to confirm hemophilia B carrier diagnosis of a complete deletion of the F9 gene - Adoración Venceslá; María Jesús Barceló; Manel Baena; Manuel Quintana; Montserrat Baiget; Eduardo F. Tizzano (Haematologica, 2007)
Approximately 3% of hemophilia B patients have major deletions in the F9 gene, half of which are complete. Marker and quantitative PCR analyses were employed for carrier diagnosis in a family of a mentally retarded hemophilia B patient with a total deletion of the F9 gene and neighbor genes. Both methodologies allowed the confirmation of carrier or non-carrier status.